318OBoth low and high blood tumour mutational burden are favourable predictors with atezolizumab. (24th November 2019) - Nie, W; Han, B
Abstract: Background: A recent study has demonstrated that high blood tumor mutational burden (bTMB) was associated with significant improvements in PFS from atezolizumab in NSCLC. However, a prospective, phase II, B-F1RST study did not confirm the result. Multiple genetic mutations may result in resistance to therapy, including immunetherapy. Therefore, we speculated that low bTMB might be a favorable prognostic biomarker for immunetherapy and both high and low bTMB patients could derive benefit from atezolizumab. We thus investigated the non-linear association between bTMB and PFS, and tried to find new cut-off values. Methods: This study used the clinical and bTMB data from POPLAR (n = 105, training set) and OAK (n = 324, validation set) studies. The non-linear association between bTMB and PFS was assessed using restricted cubic spline (RCS). The cut-off values for bTMB were calculated by using X-tile software. Results: In training set, bTMB showed an upside down J shape curve with PFS in RCS plot, suggesting a non-linear relationship between bTMB and PFS (P for non-linear < 0.001). The cut-off values of bTMB for predicting PFS were 7 and 14 mutations/Mb, and all patients were claasified into low (≤ 7 mutations/Mb), medium (8 ≤ bTMB ≤ 13 mutations/Mb), and high bTMB (≥ 14 mutations/Mb) groups according to the cut-off values. The median PFS and OS of patients with low and high bTMB were significantly longer than those of patients with medium bTMB in multivariate analysis. Similar results were shown in the validation set and the combined set (Table). Conclusions: There was a non-linear association between bTMB and survival in NSCLC patients receiving atezolizumab. Both high and low bTMB were associated with better clinical benefit with atezolizumab. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.